Concept by Concept Learning of Fuzzy Cognitive Maps - Furkan Dodurka, M.; Engin Yesil; Cihan Öztürk; Ahmet Sakalli; Cagri Guzay (Springer Berlin Heidelberg, 2013)
Fuzzy cognitive maps (FCM) are fuzzy signed directed graphs with feedbacks; they are simple and powerful tool for simulation and analysis of complex, nonlinear dynamic systems. However, FCM models are created by human experts mostly, and so built FCM models are subjective and building a FCM model becomes harder as number of variables increases. So in the last decade several methods are proposed providing automated generation of fuzzy cognitive maps from data. The main drawback of the proposed automated methods is their weaknesses on handling with large number of variables. The proposed method brings out a new strategy called concept by concepts approach (CbC) approach for learning of FCM. It enables the generation of large sized FCM models with a high precision and in a rapid way using the historical data.
Keywords: density; learning; global optimization; [INFO] Computer Science [cs]; Fuzzy cognitive maps